Hypoxia inducible factor (HIF) as a model for studying inhibition of protein–protein interactions. Issue 6 (26th April 2017) - Burslem, George M.; Kyle, Hannah F.; Nelson, Adam; Edwards, Thomas A.; Wilson, Andrew J.
Abstract : The state of the art in identifying protein–protein interaction inhibitors of hypoxia inducible factor – a promising target for anticancer drug design – is described. Abstract : The modulation of protein–protein interactions (PPIs) represents a major challenge in modern chemical biology. Current approaches ( e.g. high-throughput screening, computer aided ligand design) are recognised as having limitations in terms of identification of hit matter. Considerable success has been achieved in terms of developing new approaches to PPI modulator discovery using the p53/ h DM2 and Bcl-2 family of PPIs. However these important targets in oncology might be considered as "low-hanging-fruit". Hypoxia inducible factor (HIF) is an emerging, but not yet fully validated target for cancer chemotherapy. Its role is to regulate the hypoxic response and it does so through a plethora of protein–protein interactions of varying topology, topography and complexity: its modulation represents an attractive approach to prevent development of new vasculature by hypoxic tumours.